Five one-act plays - Byrne, Donn, 1929-; Long, Chris (Harlow, England : Pearson Education, 2000)
"Has Mrs Brown killed Granny on the beach? Why does Mrs Hill want to leave her husband? Who wants to steal the Professor's invention? And what is little Johnny trying to say? Discover the answers when you read the plays in this book. They are plays about ordinary people and the unusual, often funny, things that happen to them." - back cover
Introduction -- Listen to the boy! -- The right person -- An afternoon on the beach -- A bad dream -- The professor -- Activities
Original / British English Has Mrs Brown killed Granny on the beach? Why does Mrs Hill want to leave her husband? Who wants to steal the Professor's invention? And what is little Johnny trying to say? Discover the answers when you read the plays in this book. They are plays about ordinary people and the unusual, often funny, things that happen to them.
Keywords: Readers for new literates; One-act plays, English; Readers -- One-act plays, English